Extra skeletal chondroma a rare presentation in the big toe of a pediatric patient: a case report - Mostafa, Maged; Khamis, Ahmed R.; Aljeeran, Omar; Saqer, Waleed Yusuf; Almasry, Mohamed (International Journal of Research in Orthopaedics, 2024)
Extra-skeletal chondroma is a rare benign tumor of juxta-articular soft tissues rarely seen in pediatric cases. It is formed mainly of hyaline cartilage and presented as a painless swelling. It is not well evident on conventional X-rays radiography. MRI is the preferred diagnostic modality. Surgical excision is the recommended form of treatment for symptomatic cases. We are reporting a case of this rare tumor in the big toe of a child.